MARIA VAYNO'S SHORT FILM “YOU ARE MY SON!” – AN ODE TO HUMANITY AND COMPASSION - Melnyk, Marta (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2026)
The purpose of this article is as follows: since researchers of contemporary literary trends – and, in particular, the work of Maria Vaino – have most often focused on the distinct characteristics of the author’s short, medium-length, and long prose works, and the least attention has been paid to her film novellas, we analyze the work “You Are My Son!”, which is a symbiosis of the literary genre of short epic – the novella – and cinema, specifically the film screenplay. Hence the scientific novelty of the proposed analysis. Selected research methods: concrete-historical, receptive aesthetics, and hermeneutic. The practical significance of the article lies in a concrete contribution to the study of the writer’s artistic oeuvre, as she fruitfully continues the traditions of Oleksandr Dovzhenko, first and foremost, as well as Yurii Yanovskyi, who both pioneered and simultaneously created both works of fiction and screenplays in Ukrainian literature and cinema.